Model of National Identity Construction: The Dynamics of National Identity Formation in Archipelagic Cultural Heritage Research - Wuri, Handoko; Syamsurijal; Muh., subair; Frandus; Mu’jizah; Mukhamdanah; Hikmana Arafah , Wiryandara; Mukhammad , Isnaeni (Badan Riset dan Inovasi Nasional (BRIN), 2025)
The cultural heritage of Indonesia is a key component of the nation’s identity. Therefore, the nation's identity is characterized by its cultural heritage. This paper analyzes the results of research on the theme of cultural heritage conducted by the Literary Language Archaeology Research Organization, BRIN, covering the fields of archaeology, literary language, manuscripts, oral tradition, and religious and civilizational treasures. The research employs a mixed-methods approach, combining qualitative and quantitative methods. Data were collected through Focus Group Discussions (FGDs) and analytical reviews of 34 research reports. The research analysis shows that cultural heritage, in the form of tradition, art, language, religion, and other cultural values, plays an essential role in fostering a sense of pride, unity, and national identity. Thus, identity is constructed through a historical process involving various parties acting as members of the culture. The analysis also explains the current research model and provides conceptual frameworks for policy research, development and, basic research development, as well as for the development of measurable issues, which can inform the implementation of future research with a focus on cultural heritage and identity construction. The studies also emphasize the importance of preserving cultural heritage as a form of national identity, and as a principle of ecological ethics and social cohesion amidst global change dynamics.